Pengaruh Jumlah Uang Beredar dan Tingkat Suku Bunga terhadap Inflasi Kalimantan Timur - Akbar Lufi Zulfikar; Theresia Militina; Agus Junaidi (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2017)
Effect of money supply and interest rates to inflation in East Borneo, under the guidance of Mrs. Theresia Militina and Mr. Agus Junaidi. This study aimed to determine the effect of money supply and interest rates to inflation in East Borneo. The theory used Quantity Theory Irving Fisher and Theory Gibson Paradox. The study was conducted by using a multiple linear regression. Further testing of the hypothesis with the t test to see the effect of independent variables on the dependent variable individually is on the money supply variable (X1) from the calculation, a significant value 0.046 0.05, indicates that the variable money supply have a significant effect on inflation (Y), while the variable interest rates (X2) from the calculation, a significant value 0.005 0.05, indicates that the variable interest rates have a significant effect on inflation (Y).Keywords : Money Supply, Interest Rates and Inflation